Perempuan Pekerja Industri Tahu Tempe di Desa Sikur Kecamatan Sikur Kabupaten Lombok Timur - Yusni, Wahyudi; ZM, Hamidsyukrie; Masyhuri, Masyhuri; Syafruddin, Syafruddin (Jurnal Ilmiah Global Education, 2024)
The objectives of the study are: (1) The employment status of women workers in the tofu tempe industry, (2) The workload faced by women workers in the tofu tempe industry, (3) The benefits of the tofu tempe industry for women workers both for themselves and the family economy. This research uses a qualitative approach of the case study method. The types of data in this research are primary data and secondary data. The data collection techniques used were interviews, observation, and documentation. Data analysis is qualitative with the stages of data reduction, data presentation, and conclusion drawing. The results of the study found that: (1) The employment status of women workers in the tofu and tempeh industry is casual workers and hired workers. (2) The workload of women workers in the tofu tempeh industry is productive and reproductive. (3) The benefits of the tempeh tofu industry for women’s work both for themselves and the family economy are increasing husband’s income and family income, daily family shopping needs, children’s school fees, saved for other important family needs.